O esvaziamento do sagrado em Miguel Torga - Ferreira, Vagner da Silva (2013)
The literature has much examples which represents the religious universe. But this representation clashes, anyway, from the consolidated religious patterns and, like this, this sacred may seems an emptied way. This work intends to do a discussion of the existence sacred in the literature, analyzing more specifically, in the Miguel Torga´s writing. First time, we discuss the meaning of the sacred to the man; how it stay in religious universe and, still, the different faces of the ways how both – the sacred and the man – interact. Next, we have the view of the sacred presence in torguiana´s poetry, beyond the discussion how Torga represents the sacred and the man in his texts, pretending understanding the strategies and literary characteristics of the Portuguese writer, constituents of a writing that intend emphasize the man instead of the sacred, following a discussion about the Torga´s man, that can be pointed like universal. Finally, we made the analyses from the chosen tales that are in the books Contos da montanha and Novos contos da montanha, that the sacred presence is evident. This way we have an interpretation work or interpretations suggests about the empting of the sacred in torguiano´s tales.